Lockdown Changed Us in Turkey Eating Behaviors, Depression Levels, and Body Weight Changes during Lockdown: An Online Survey in Turkey - Çakır Biçer, Nihan; Baş, Murat; Köse, Gizem; Şenol Duru, Pırıl; Baş, Dilşat; Karaca Çelik, Esen; Köseoğlu, Selen (Progress in Nutrition, 2021)
Nationwide lockdown is a proven strategy to decrease inters human transmission of the COVID-19. Prolonged home stay may be associated with some potential side effects as weight gain, depression, physical inactivity, unbalanced diet, and behavioral addiction disorders. During March-May of the social lockdown, Turkish adults (N=2955) completed an online sociodemographic form, Beck Depression Inventory (BDI) and Three Factor Eating Questionnaire (TFEQ). During lockdown, 51.1% of the participants gained weight and TFEQ, emotional and uncontrolled eating scores were increased (p<0.001). Analysis showed that body weight increase was significantly related to the TFEQ score, depression level, having a disease, decreased exercise, increased alcohol consumption, dismissal from work and reduced smoking (p<0.001). There were significant changes in uncontrolled eating, emotional eating, and cognitive restriction during the lockdown period. Additionally, changes in eating habits and physical activity may influence weight gain.